TO SELECTION OF MACHINERY SETS FOR FUEL SUPPLY OF BIOMASS POWER UNITS - A. V. Vavilov; M. N. Pashkovsky; Yu. V. Sokohvsky; S. M. Siniak; V. N. Tsybulko (Наука и техника)
The following problem is formulated that by 2012 it is necessary to increase usage of local fuel types in power balance of Belarus up to 25%. One of the local power source is biomass. However, while resizing the formulated problem, we are racing some difficulties: unpreparedness of production, absence of special efficient equipment for production and transportation of wood fuel. Application of the available equipment leads to significant expenses that increases cost of the local fuel even by 2-3 fold. The paper considers the available technical facilities for laying-in wood fuel. The efficient machinery sets for fuel supply of biomass power units in Belarus are proposed in the paper.